Extracting word-like units when two concurrent regularities collide: electrophysiological evidence - Soares, Ana Paula (2021)
Statistical learning (SL) is a fundamental skill assumed to play a central role in the acquisition of the rule-governed aspects of language. Despite evidence that SL is present from early infancy to support the extraction of sound patterns in speech, the nature of the computations involved is unclear. Here we collected electrophysiological data while preschool children were exposed to an auditory stream in which two concurrent regularities were embedded, firstly, under accidental (implicit), and, subsequently, under intentional (explicit) conditions. Results showed that the extraction of sound patterns was enhanced by the effect of explicit instructions and, critically, that under this conditions, children seem to rely on the computation of syllable frequency rather than on transitional probabilities to extract word-like units.